A supporting ecosystem to mature extracellular vesicles into clinical application. (12th April 2019) - De Wever, Olivier; Hendrix, An
Abstract : Research into extracellular vesicles (EV) has yielded important biological insights and raised the prospect of developing novel diagnostics and therapeutics for a wide range of pathologies. As with other emerging and transformative fields in research, it will require a broad, supportive base for EV research to mature and to develop clinical application. Here, we identify several focus areas to further improve reproducibility and reliability specifically for EV research and make recommendations for minimal experimental guidelines, transparency tools, reference materials, validation, identification of contaminants, data sharing, coaching through education, and funding opportunities. Abstract : Research on Extracellular Vesicles (EV) holds great potential for developing diagnostic and therapeutic applications for a wide range of diseases. The authors define eight pillars and propose minimal guidelines for good laboratory practice and to improve experimental reproducibility and reliability in EV research.